HISTOLOGICAL CHANGES OF ADRENAL GLAND IN RABBITS DURING THE EXPERIMENTAL INFECTION WITH TRYPANOSOMA EVANSI AND AFTER TREATMENT WITH NAGANOL - Hussein, S. M. (The Iraqi Journal of Veterinary Medicine, 2021)
The structural – functional changes in the adrenal glands associated with experimental infection with Trypanosoma evansi and the reversed changes after the treatment of rabbits with anti-trypanosomal drugs (Naganol, Bayer, 205) were studied. Thirty adult New Zealand male rabbits were divided into two groups: control group which include 12 rabbits while the infected group include 13 rabbits. Rabbits of infected group were injected I. V with 10 trypanosoma on 0.2 ml mice blood diluted with AL -sever’s solution while rabbits of control group were injected with trypansoma free diluted mice blood. Forty-two days after infection the infected group were treated with neganol 10% sol. (20mg/ kg B.W, i.v) than all the rabbits were killed after 42 days of treatment. Microscopic examination of the hematoxylin-eosin stained adrenal gland revealed occurrence of degenerative changes of the zona fosciculata-reticulaties infltration of mononuclear cells, red blood cells and focal coagulative necrosis in both zone when compared with those of the control group, while treated group showed focal regeneration of secretort cells of both zone. It is concluded there were revers of structural-functional changes after treatment to the normal state.